2013
DOI: 10.1080/01140671.2013.807853
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cowpea (Vigna unguiculata) intercropping on weed biomass and maize (Zea mays) yield

Abstract: Field experiments were conducted to investigate the influence of cowpea (Vigna unguiculata) density (0, 15 or 30 plants/m 2 ) and sowing date (15 days prior to maize sowing or simultaneously with maize), and of maize (Zea mays) planting density (7.5 or 9 plants/m 2 ) on weed biomass and maize crop yield. Results showed that increasing the maize density from 7.5 to 9 plants/m 2 reduced the weed biomass by 21.5%. Furthermore, cowpea acted as a living mulch, reducing weed biomass by up to 45.5% and 39.6% when int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 22 publications
3
11
0
3
Order By: Relevance
“…Lack of available uncovered, inter-row spaces for weed establishment resulted in a severe reduction in the biomass of weeds. Many studies reported lower dry weights of weeds in systems that use cover crops because of covering the inter-row spaces (Teasdale and Mohler, 1993;Jamshidi et al, 2013). In the present study, weed infestation was generally reduced, as the density of cover crop increased ( Figs.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Lack of available uncovered, inter-row spaces for weed establishment resulted in a severe reduction in the biomass of weeds. Many studies reported lower dry weights of weeds in systems that use cover crops because of covering the inter-row spaces (Teasdale and Mohler, 1993;Jamshidi et al, 2013). In the present study, weed infestation was generally reduced, as the density of cover crop increased ( Figs.…”
Section: Discussionsupporting
confidence: 60%
“…1 and 2). Previous research demonstrated that cover crop density influenced weed biomass (Jamshidi et al, 2013). Increasing crop densities lead to early closure of crop canopy and help to maximize crop competiveness (Monaco et al,Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced weed growth observed under cowpea live mulch may be attributed to early growth of the crop and ground coverage which may have resulted in physical interference on weed seed germination and seedling growth and competition for light, water, and nutrients. Jamshidi et al (2013) and Talenneigi and Ghadiri (2012) also reported that cowpea live mulching greatly reduced the density and dry weight of the weeds.…”
Section: Resultsmentioning
confidence: 96%
“…Sistem tumpangsari dengan tanaman yang memiliki morfologi daun yang lebar seperti legume, mampu menekan pertumbuhan gulma (Eskandari dan Kazemi, 2011;Gharineh dan Moosavi, 2010;Khan et al, 2012). Jamshidi et al (2013) menjelaskan bahwa terjadi pengurangan kepadatan dan perubahan komunitas gulma di bawah tegakan tanaman sistem tumpangsari jagung (Zea mays) -kacang tunggak (Vigna unguiculata) akibat adanya penutupan tanah yang sempurna oleh tajuk tanaman kacang tunggak. Perubahan komunitas gulma terjadi selama proses pertumbuhan tanaman yang disebabkan oleh sinar matahari yang mampu menembus sampai ke permukaan tanah.…”
Section: Pendahuluanunclassified